2020
DOI: 10.1108/ajim-10-2019-0304
|View full text |Cite
|
Sign up to set email alerts
|

Why we like Google Scholar: postgraduate students' perceptions of factors influencing their intention to use

Abstract: PurposeThis study examines the use of the search engine, Google Scholar, from the perspective of a specific study group, that of international postgraduate students. Based on the theory of task perceived performance and effort expectancy influencing intention to use, further factors of system, individual, social and organisational, in the postgraduate student context are explored. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…This rather speculative assumption of a current retrieval paradigm may be propped up by the observation that the 'ideal' type of a variety-enhancing tool does not even seem to exist yet: there is not yet the fictitious bot that spits out random scientific publications from a huge corpus from centuries of publications of which each work has an equal probability of being listed, regardless of the publication's age, discipline, authors, citational impact or publication outlet. In addition, one of the most frequently used machines for research discovery, Google Scholar [59], is by default a query-based and, therefore, a redundancy-reproducing one (it is even partly citation-based, as it sorts results based on algorithms that take into account the number of citations by default).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This rather speculative assumption of a current retrieval paradigm may be propped up by the observation that the 'ideal' type of a variety-enhancing tool does not even seem to exist yet: there is not yet the fictitious bot that spits out random scientific publications from a huge corpus from centuries of publications of which each work has an equal probability of being listed, regardless of the publication's age, discipline, authors, citational impact or publication outlet. In addition, one of the most frequently used machines for research discovery, Google Scholar [59], is by default a query-based and, therefore, a redundancy-reproducing one (it is even partly citation-based, as it sorts results based on algorithms that take into account the number of citations by default).…”
Section: Discussionmentioning
confidence: 99%
“…In effect, if researchers only used, say, Google Scholar and Mendeley Suggest to discover relevant publications, they would probably reproduce bibliometric redundancy – as is visible in the standard assumption of a Pareto distribution in bibliometrics, according to which 80% of all citations go to just 20% of all research outputs ([5961]; but note that there is evidence of a gradual change in this pattern, cf. [62]).…”
Section: Discussionmentioning
confidence: 99%
“…It is proven in the small amount of literature we found, even in Google Scholar, which database is more comprehensive than others. As a competent Big Data device, Google continuously updates its performance by improving the database based on academics' criticisms for better service [13], [14].…”
Section: Methodsmentioning
confidence: 99%
“…UTAUT has been validated extensively in learning and Kaliisa et al (2019) suggested that UTAUT is effective in investigating mobile learning acceptance. For example, Alotaibi and Johnson (2020) examined international postgraduate students' intention to use Google Scholar based on the four constructs of UTAUT. Moreover, Alowayr (2022) extended the UTAUT to investigate mobile learning acceptance in Saudi Arabia and achieved good results.…”
Section: Open Datamentioning
confidence: 99%